2013
DOI: 10.1177/1363461513503381
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicide ideation and attempts among Black Americans in later life

Abstract: This article provides the first national estimates of the prevalence and correlates of nonfatal suicidal behavior among older Black Americans. There is a lack of national data on suicide ideation and attempts across ethnic classifications of Blacks in a nationally representative sample. Data are a subsample from the National Survey of American Life (NSAL), a national U.S. adult household probability sample of 5,191 Black Americans. The WHO Composite International Diagnostic Interview (CIDI) was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…The finding of our study demonstrates that suicidal ideation was a significant public health concern among U.S. Chinese older adults. In a recent national representative study of 5,191 African American older adults aged 55 years and above, the prevalence of lifetime suicidal ideation was lower (6.1%) than that of our study (9.4%; Joe, Ford, Taylor, & Chatters, 2014). Lifetime suicidal ideation was also higher than studies conducted among Chinese older adults older adults in Hong Kong (5.5%) and Beijing (2.2% ; Ma et al, 2009; Yip et al, 2003).…”
Section: Discussioncontrasting
confidence: 93%
“…The finding of our study demonstrates that suicidal ideation was a significant public health concern among U.S. Chinese older adults. In a recent national representative study of 5,191 African American older adults aged 55 years and above, the prevalence of lifetime suicidal ideation was lower (6.1%) than that of our study (9.4%; Joe, Ford, Taylor, & Chatters, 2014). Lifetime suicidal ideation was also higher than studies conducted among Chinese older adults older adults in Hong Kong (5.5%) and Beijing (2.2% ; Ma et al, 2009; Yip et al, 2003).…”
Section: Discussioncontrasting
confidence: 93%
“…Furthermore, the sample of this study was not representative of the United States (U.S.), so the results should not be generalized to the racial landscape of suicide in the U.S. In addition, our list of variables was not a comprehensive list [ 4 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Several relevant constructs, including other risk factors of suicide, were not evaluated.…”
Section: Limitationsmentioning
confidence: 99%
“…Taking countries with different levels of economic development as examples, a nationwide cross-sectional survey in South Korea, including 58,590 elderly, showed 15.72% prevalence of SI [53]; In Mexico, belonging to developing countries, a cross-sectional survey on elderly aged 65 years and older found 13.5% lifetime prevalence of SI [54]. However, one national survey that included 5,191 older Black Americans showed that the lifetime prevalence of SI was only 6.1% [55]. The reasons for the high prevalence of SI among the Chinese elderly may be that, rstly, rapid urbanization has, to some extent, dissolved traditional Chinese clan ties, exacerbating the loneliness and even depression of the elderly, especially those left behind, which may further lead to SI; secondly, China has a large elderly population, but mental health services have di culty in meeting such a large demand; thirdly, in the unique Chinese culture, the elderly are often reluctant to trouble their young children, and SI has a certain stigmatizing effect, which may lead to the elderly not seeking help in time when they have psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence was higher in the female, advanced age, not married, and illiterate groups than in their corresponding subgroups but was not statistically signi cant; (2) Physical condition: the prevalence of SI was signi cantly higher in the elderly with chronic disease, activities of daily living (ADL) disability, and poorer physical health than in their corresponding subgroups; (3) Mental condition: the prevalence of SI was signi cantly higher among the elderly with depression symptoms and lower life satisfaction than in their corresponding subgroups; (4) Living and economic condition: the prevalence of SI among the elderly with poorer economic status (15.41%, 95% CI 8. 55…”
Section: Subgroup Analysis On the Prevalence Of Simentioning
confidence: 99%